The US 2016 presidential election & Russia's troll farms. Issue 1 (2nd January 2020) - McCombie, Stephen; Uhlmann, Allon J.; Morrison, Sarah
ABSTRACT: The Russian Internet Research Agency (IRA) prosecuted an online campaign to undermine the 2016 US presidential election. It sought to accentuate existing social conflicts to affect the electoral behaviour of select groups. However, the IRA's actual effect on the election outcomes, as assessed through its effect on its specifically targeted regions, was minimal. Nonetheless, the Kremlin successfully exploited the shock of Trump's victory to exaggerate the apparent effect of Russian intervention. By seemingly fecklessly denying an apparently successful covert action, Moscow further challenged the legitimacy of the US election and degraded the coherence of US strategic decision making.